STATISTICAL ANALYSIS OF GROWTH CONDITIONS OF NEWLY ISOLATE BACILLUS SP. PRODUCING L-ASPARAGINASE - Jimat, Dzun Noraini; Mohamed, Intan Baizura Firda; Azmi, Azlin Suhaida; Amid, Azura (IIUM Engineering Journal, 2020)
The concentrations of nutrient elements together with several physical parameters were screened to find out the significant factors for the production of L-asparaginase from newly isolated strain, Bacillus sp. from Sg Klah, Hot Spring, Perak. Then, the significant factors were optimized for enhancing L-asparaginase production from the bacterium strain. Two statistical designs, Two Level Factorial Design and Face Centered Composite Design (FCCD), Design expert @version 8.0 were employed in screening and optimization of the process variables, respectively. The results for all experiment runs were analyzed by analysis of variance (ANOVA). Peptone (nitrogen source) concentration and temperature were found as significant factors, positively influenced the production of L-asparaginase. The two factors were then optimized to increase the desired enzyme production. The optimum peptone concentration and the temperature were found at 1.4 g/L and 30ºC, respectively. The L-asparaginase production under optimized conditions increased from 0.15±0.023 U/mL to 0.19 ± 0.03 U/mL. The kinetic studies showed that the biomass production dropped after 24 hours while L-asparaginase activity is active and positively increased until the fermentation period ended. ABSTRAK: Kepekatan unsur-unsur nutrien bersama-sama dengan beberapa parameter fizikal telah diteliti untuk mengetahui faktor-faktor penting untuk pengeluaran L-asparaginase dari spesis baru diasingkan, bacillus sp. dari kolam air panas tempatan. Kemudian, faktor penting dioptimumkan untuk meningkatkan pengeluaran L-asparaginase daripada bakteria tersebut. Two Level Factorial Design dan Face Centered Composite Design (FCCD), Design expert @version 8.0 telah digunakan dalam penyaringan dan pengoptimuman pembolehubah proses dalam kajian ini. Keputusan untuk semua eksperimen dianalisis dengan analisis varians (ANOVA). Kepekatan dan suhu peptone (sumber nitrogen) didapati sebagai faktor penting, secara positif mempengaruhi pengeluaran L-asparaginase. Kedua-dua faktor ini dioptimumkan untuk meningkatkan pengeluaran enzim yang dikehendaki. Kepekatan peptone dan suhu optimum didapati masing-masing pada 1.4 g / L dan 30ºC. Pengeluaran L-asparaginase di bawah keadaan yang dioptimumkan meningkat dari 0.15 ± 0.023 U / mL kepada 0.19 ± 0.03 U/mL. Kajian kinetik menunjukkan bahawa pengeluaran biojisim menurun selepas 24 jam manakala aktiviti L-asparaginase aktif dan meningkat secara positif sehingga tempoh penapaian berakhir.